Enhancement in c-Si solar cells using 16 nm InN nanoparticles - ALEVLİ, MUSTAFA (IOP PUBLISHING LTD, 2016)
In this work, 16 nm indium nitride (InN) nanoparticles (NPs) are used to increase the performance of thin-film c-Si HIT solar cells. InN NPs were spin-coated on top of an ITO layer of c-Si HIT solar cells. The c-Si HIT cell is a stack of 2 mu m p type c-Si, 4-5 nmn type a-Si, 15 nm n(+) type a-Si and 80 nm ITO grown on a p(+) type Si substrate. On average, short circuit current density (J(sc)) increases from 19.64 mA cm(-2) to 21.54 mA cm(-2) with a relative improvement of 9.67% and efficiency increases from 6.09% to 7.09% with a relative improvement of 16.42% due to the presence of InN NPs. Reflectance and internal/external quantum efficiency (IQE/EQE) of the devices were also measured. Peak EQE was found to increase from 74.1% to 81.3% and peak IQE increased from 93% to 98.6% for InN NPs coated c-Si HIT cells. Lower reflection of light due to light scattering is responsible for performance enhancement between 400-620 nm while downshifted photons are responsible for performance enhancement from 620 nm onwards.
Keywords: solar cells; photoluminescence; downshifting; scattering; ELECTRICAL-PROPERTIES; DOWN-CONVERSION; THIN-FILMS; SILICON; PERFORMANCE; EFFICIENCY; NANOCRYSTALS; WAVELENGTH; DEPOSITION; INCIDENT